Kontribusi Program Pelatihan Gaya Kepemimpinan dan Kepuasan terhadap Kinerja Guru Madrasah Aliyah KKMA 02 Kabupaten Jepara. - Masluri, Masluri (2010)
Objective is to test and analyze the contribution of the Training, Job Satisfaction Leadership Style on Performance of High School Teachers Jepara simultaneously and partially The study was a quantitative research expo facto. The population in this study were teachers of high school, amounting to 469 teachers from 23 high schools, with a limit of error of 5%, then the total sample of 222 teachers was obtained from the table Slovin. Determination of sampling this study using proportional stratified random method (proportional stratified random sampling). Data collection tool that is used is to use a questionnaire or a questionnaire. Technical analysis performed by multiple linear regression analysis of data is a prerequisite test, normality, multikoleniaritas test, accuracy test model, the coefficient of determination, partial test. The results showed: (1) there is variable contribution of training programs, leadership style, satisfaction with the performance of high school teachers Jepara this simultaneously demonstrated the significant value of 0.000<0.05. With the value of R square of 6.27 indicates that the simultaneous contribution of training programs, leadership style, job satisfaction of teachers' performance of 62.7%, while the remaining 37.3% is explained by other variables not studied, (2) there was a variable contribution Training Programme to performance tcount> ttable (7.08> 1.65), (3) is the contribution of leadership style on teacher performance, with the obtained tcount>ttable (10.43>1.66), (4) is the contribution of Job Satisfaction of Teacher Performance obtained tcount>ttable (5.04>1.66), then Ho is rejected, while Ha accepted.